Synchronous osseous metastasis, degenerative changes, and incidental multifocal Paget's disease in a case of newly diagnosed prostatic carcinoma - Robert Devita; Kaushik Chagarlamudi; Arash Kardan (World Journal of Nuclear Medicine)
Tc-99m methylene diphosphonate bone scintigraphy (bone scan) is a highly sensitive technique for the evaluation of osseous pathology. However, the nonspecificity of the method can present diagnostic challenges in differentiating benign from malignant processes. Often, Paget's disease and osseous metastasis can coexist in elderly patients. Therefore, it is important to accurately distinguish the two pathologies, as each has a different prognosis and impacts clinical management. Obtaining the appropriate clinical diagnosis often involves a combination of laboratory, radiographic, and clinical data. We present a case of newly diagnosed prostatic carcinoma presenting with synchronous osseous metastasis, degenerative changes, and incidental multifocal Paget's disease.